The Efficacy and Immunogenicity of COVID-19 Vaccine: Special Focus on Patients with Cancer - Abdukalykovna, Israilova Zeinep; Shaker, Alhamza Abdulsatar; Naser, Sanarya Thamer; Hussein, Ahmed M.; Al‑Hilfi, Thamer; Rahim, Fakher (Trends in Immunotherapy, 2025)
Research indicates that immunization is the most efficacious approach for stopping the transmission of COVID-19. This study aims to offer immunization recommendations for patients with autoimmune/autoinflammatory rheumatological disorders, immunodeficiencies, cancer, diabetes, chronic respiratory, and cardiovascular diseases. The intended audience includes doctors, medical personnel, and patients. This review study involved conducting a search in scholarly electronic databases, including ISI, Google Scholar, Scopus, and PubMed. The issue of COVID-19 vaccinations and the vaccination of patients with certain disorders was informed by the latest and pertinent authoritative publications published between 1980 and 2024. When autoimmune illness patients effectively manage their disease activity and there is no concurrent infection, they should receive the COVID-19 vaccination. Low-intensity immunosuppression does not reduce the antibody response to vaccinations. Immunization using all forms of vaccination, excluding live attenuated vaccines, is efficacious for all individuals with cancer, except for those undergoing anti-B cell therapy. Additionally, it is recommended to administer vaccinations to individuals who have underlying conditions such as obesity, cardiovascular diseases, respiratory diseases, and diabetes, as these conditions heighten the chance of developing severe cases of COVID-19. To combat the COVID-19 virus, the most effective approach is to increase vaccination coverage in order to stimulate immune responses. This paper provides a thorough examination of the latest developments and existing challenges in the area of COVID-19 vaccines against cancer. Additionally, it explores the prospective future uses of vaccines in cancer immunotherapies.